(untitled) (International Seven Journal of Multidisciplinary, 2024)
A number of factors have a direct impact on the efficiency and productivity of teams, as well as on organizational health, which is why the crucial role of leadership in team management stands out, emphasizing the ability of leaders to motivate and drive their teams towards common goals, creating an environment conducive to collaboration and commitment. This leadership role is recognized as a key strategic differentiator for organizational success in a highly competitive market. As such, we have posed the following question: What are the impacts of leaders on team management and how do they contribute to a company’s productivity? The aim of this study is to understand the importance of the leader’s role in managing teams in a company. Methodologically, it is a qualitative bibliographic review, using secondary data collection from renowned authors on the subject. Furthermore, this research reinforces the idea that team management goes beyond the supervision of tasks, involving the creation of an environment conducive to growth, innovation and collaboration so that there is an environment of development and collective learning, which will be reflected in the company’s productivity.